2021
DOI: 10.3390/ph14070636
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pyrimethamine and Cycloguanil Analogues as Dual Inhibitors of Trypanosoma brucei Pteridine Reductase and Dihydrofolate Reductase

Abstract: Trypanosoma and Leishmania parasites are the etiological agents of various threatening neglected tropical diseases (NTDs), including human African trypanosomiasis (HAT), Chagas disease, and various types of leishmaniasis. Recently, meaningful progresses in the treatment of HAT, due to Trypanosoma brucei (Tb), have been achieved by the introduction of fexinidazole and the combination therapy eflornithine–nifurtimox. Nevertheless, due to drug resistance issues and the exitance of animal reservoirs, the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 57 publications
2
24
0
1
Order By: Relevance
“…Although lower activity was demonstrated against T. b. brucei crude protein extract, the results nevertheless portrayed a consistent inhibition of the oxidation of the NADPH cofactor by the parent hit (MMV675968) and the two promising analogs (MMV1578467 and MMV1578445) ( Figure 7 ). The effective but low activity compared to previously reported data [ 28 , 47 ] could be tentative justified by the fact that a crude protein extract was used in the assays rather than the purified DHFR enzyme. Future in vitro/in vivo studies using recombinantly purified DHFR enzyme and appropriate animal models of trypanosomiasis will enable us to confirm our assertions.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although lower activity was demonstrated against T. b. brucei crude protein extract, the results nevertheless portrayed a consistent inhibition of the oxidation of the NADPH cofactor by the parent hit (MMV675968) and the two promising analogs (MMV1578467 and MMV1578445) ( Figure 7 ). The effective but low activity compared to previously reported data [ 28 , 47 ] could be tentative justified by the fact that a crude protein extract was used in the assays rather than the purified DHFR enzyme. Future in vitro/in vivo studies using recombinantly purified DHFR enzyme and appropriate animal models of trypanosomiasis will enable us to confirm our assertions.…”
Section: Discussionmentioning
confidence: 80%
“…Post docking analyses revealed that, in DHFR, all the accessible protonation states of both compounds shared similar poses within the same ligand recognition site in the binding pocket. This resulted in hydrogen bond formation between the diaminopyrimidine moiety and key DHFR ligand recognition residues [ 26 , 27 , 28 ], including the highly conserved Val32 ( Figure 3 A,B). Unlike DHFR, the TR enzyme consists of a wide binding site, where substrates and inhibitors have been shown to adopt different conformations with stacking observed for some inhibitor binding poses [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…These periods are potentiated by unrestricted large-scale use of the drug, inaccurate dosing regimens, and use of drugs that are slowly eliminated from the body. Drug-specific selection mechanisms normally follow the primary low impact generic resistance mechanisms associated with increased stress responses [ 87 ]. When drug-specific resistance events appear, the increase in the drug concentration will only lead to a greater selective pressure resulting in higher levels of resistance.…”
Section: Drug Resistance In T Bruceimentioning
confidence: 99%
“…Post docking analyses revealed that, in DHFR, all the accessible protonation states of both compounds shared similar poses within the same ligand recognition site in the binding pocket. This resulted in hydrogen bond formation between the diaminopyrimidine moiety and key DHFR ligand recognition residues [35][36][37], including the highly conserved Asp54, and Val32 (Figs 3A and 3B). Unlike DHFR, the TR enzyme consists of a wide binding site, where substrates and inhibitors have been shown to adopt different conformations with stacking observed for some inhibitor binding poses [38,39].…”
Section: Accessible Protonation States Of the Compounds And Molecular...mentioning
confidence: 99%